Recurrent invasive ductal carcinoma of the breast with metastasis to the uterine cervix: A case report - Alexander Dye; Vasanti Jhaveri; Savas Ozdemir; Ahmad Alkhasawneh; Karina Hew (Elsevier, 2024)
This article presents a case of cervical metastasis from recurrence of invasive ductal carcinoma of the breast >20 years after initial diagnosis. The diagnosis was made after the patient presented with three months of intermittent post-menopausal vaginal spotting. She underwent palliative radiotherapy combined with chemotherapy and was disease free at the time of writing. Cervical metastasis of a primary breast cancer is extremely rare and can present with a variety of symptoms. This case report highlights the importance of life-long gynecologic care and surveillance in patients with a history of breast cancer.